2020
DOI: 10.3390/biomedicines8060153
|View full text |Cite
|
Sign up to set email alerts
|

Possible Correlation between Cholinergic System Alterations and Neuro/Inflammation in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an autoimmune and demyelinating disease of the central nervous system. Although the etiology of MS is still unknown, both genetic and environmental factors contribute to the pathogenesis of the disease. Acetylcholine participates in the modulation of central and peripheral inflammation. The cells of the immune system, as well as microglia, astrocytes and oligodendrocytes express cholinergic markers and receptors of muscarinic and nicotinic type. The role played by acetylcholine in MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 91 publications
0
26
0
Order By: Relevance
“…The VN stimulation suppress inflammation via cholinergic anti-inflammatory pathway. The cholinergic system has been suggested as a mediator between the nervus and immune systems and as a modulator of immune responses [ 20 , 21 ]. Thus, VN modulation may alleviate autoimmune disorders including MG and MS through acetylcholine release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VN stimulation suppress inflammation via cholinergic anti-inflammatory pathway. The cholinergic system has been suggested as a mediator between the nervus and immune systems and as a modulator of immune responses [ 20 , 21 ]. Thus, VN modulation may alleviate autoimmune disorders including MG and MS through acetylcholine release.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological/electrical stimulation of VN leads to the release of acetylcholine which suppresses the production of TNF-α and other pro-inflammatory cytokines in lipopolysaccharide-stimulated human macrophage cultures [ 19 , 20 , 21 ]. Therefore, the modulation of vagal activity may result in beneficial therapeutic effects for both MG and MS patients [ 20 , 21 ]. Conversely, the cholinergic deficit observed in MG may contribute to the intensification of the autoimmune response.…”
Section: Introductionmentioning
confidence: 99%
“…In MS patients, the expression of transcript for OCTN-1 and mediatophore, the two proteins typically expressed in immune cells and responsible for the non-vesicular ACh release, were also up-regulated, other than the ACh biosynthetic enzyme ChAT [ 79 , 80 ]. The dysregulated balance between ACh, AChE, and BChE could be responsible for higher pro-inflammatory cytokines production detected in MS patients [ 81 ].…”
Section: Cholinergic and Immune System Crosstalk In Widespread Neuro-inflammatory Diseasesmentioning
confidence: 99%
“…Studies conducted in our laboratory have demonstrated that muscarinic receptors play relevant roles both in physiological and pathological conditions [ 16 , 17 , 18 , 19 , 20 , 21 ]. In recent years, the implication of muscarinic receptors has been largely reported as novel therapeutic targets for the treatment of different forms of cancers [ 22 ].…”
Section: Introductionmentioning
confidence: 99%